Research progress of double network hydrogel in the field of bone regeneration - ZHANG Tianyi, ZHENG Yi, LYU Wenhao, MA Ning (Kouqiang yixue)
Double network(DN) hydrogels have the ability to precisely adjust physical and chemical properties, change the interaction between biomaterials and cells or biomolecules, which can better fulfill clinical needs. DN have been widely used in tissue engineering and regenerative medicine. This article summarizes the advantages of DN hydrogels used in bone tissue regeneration, and introduces the effect of DN hydrogel systems on the behavior of loading cells, drug delivering in bone reparation, and the application of DN hydrogel system in microenvironment construction, bioactive composite materials, and antibacterial activity to meet the needs of bone regeneration.